Transcriptome-based analysis reveals chromatin remodeling in post-adult eclosion reconstruction of the insect fat body - Yiying Li; Yuanyuan Hu; Bei Wang; Mengyao Lang; Shutang Zhou; Zhongxia Wu (Journal of Integrative Agriculture, 2025)
The insect fat body is comparable to the liver and adipose tissue in vertebrates, and plays a pivotal role in energy metabolism, nutrient storage, and reproduction. During metamorphosis, the fat body is disassembled via programmed cell death and cell dissociation. After adult eclosion, the fat body is reconstructed either by repopulation from the remaining juvenile fat body cells or by differentiation from adult progenitor cells. This reconstruction is a prerequisite for initiating the extensive synthesis of vitellogenin (Vg), which is necessary for the maturation of eggs. Despite its significance, the underlying mechanisms of this reconstruction remain inadequately understood. Transcriptome analysis of the fat bodies from migratory locusts at 0–5 days post adult emergence revealed 79 genes associated with chromatin remodeling. Weighted gene co-expression network analysis indicated a positive correlation between chromatin remodeling and fat body reconstitution. Protein–protein interaction analysis revealed that brahma, which encodes the catalytic subunit of the SWI/SNF chromatin remodeling complex, is crucial for post-adult-eclosion fat body development. qRT-PCR analysis demonstrated that the levels of brahma mRNA in the fat body are progressively increased during the previtellogenic stage, then reach the peak and remain elevated in the vitellogenic phase. Furthermore, brahma is expressed in response to gonadotropic juvenile hormone (JH). Knockdown of brahma led to a marked reduction in Vg expression within the fat body, along with arrested ovarian growth. These findings shed light on the involvement of brahma-mediated chromatin remodeling in JH-stimulated fat body reconstruction and reproduction of adult female locusts.